The tuned-absorber in self-excited system - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1979)
In this paper the self-excited system with tuned absorber is examined. Two kinds of absorbers have been considered: the non-resonant absorber and the resonant one. For the first kind, the self-excitation can be fully suppressed by increasing the damping coefficient: While for the second one, that may be only by making a rational choice of this coefficient. In the case of system with several degrees of freedom, the resonant absorber with several degrees of freedom can be used.